The Place of the City: Collaborative Learning, Urban History, and Transformations in Higher Education. (May 2014) - Meringolo, Denise D.
The articles in this special section illuminate the benefits and challenges of university–community partnerships. For decades, there has been a movement to facilitate collaboration among urban historians, public historians, preservationists, city planners and neighborhood activists. Those who championed such work recognized that aligning academics' agenda of research, teaching, and service with public servants' advocacy and community organizing could transform the relationship between institutions of higher learning and the neighborhoods that surround them. In recent years, several intellectual and pedagogical trends have lent legitimacy to this effort, including the rise of service learning and the promotion of civic engagement. It is crucial for institutions of higher learning to recognize the ways in which place-based research challenges traditional measures of achievement, breaking down not only barriers that have separated universities from communities but also those that have long separated research, teaching, and service.